2003
DOI: 10.1002/jnr.10563
|View full text |Cite
|
Sign up to set email alerts
|

Minimal residues in linker domain of syntaxin 1A required for binding affinity to Ca2+/calmodulin‐dependent protein kinase II

Abstract: The linker domain is important for the conformational change syntaxin 1A, which enables it to act as a SNARE for exocytosis. We found that when applied exogenously, the linker domain is a potent inhibitor of exocytosis through inhibiting interaction between autophosphorylated CaMKII and endogenous syntaxin 1A (Ohyama et al. [2002] J. Neurosci. 22:3342-3351). To identify the simplest and the most potent inhibitor for exocytosis, we further characterized the linker domain and determined the minimal number of res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…CaMKII has been shown to regulate exocytosis via a specific interaction with syntaxin (43)(44)(45)(46). In addition, syntaxin is known to bind to the most proximal region of the Kv2.1 C terminus, termed C1a, during Ca 2+ -facilitated exocytosis in pancreatic and other nonneuronal cells (47)(48)(49).…”
Section: Injurious Oxidant Exposure Leads To Camkii Activation In Neumentioning
confidence: 99%
“…CaMKII has been shown to regulate exocytosis via a specific interaction with syntaxin (43)(44)(45)(46). In addition, syntaxin is known to bind to the most proximal region of the Kv2.1 C terminus, termed C1a, during Ca 2+ -facilitated exocytosis in pancreatic and other nonneuronal cells (47)(48)(49).…”
Section: Injurious Oxidant Exposure Leads To Camkii Activation In Neumentioning
confidence: 99%
“…Reduced syntaxin 1-␣CaM kinase II and increased syntaxin 1-Munc-18 interaction in synaptic membranes after chronic antidepressants It was recently shown that syntaxin 1 reversibly binds ␣CaM kinase II and that the affinity of this interaction is greatly increased when the kinase is phosphorylated at Thr 286 (Ohyama et al, 2002;Nomura et al, 2003). It was found that the ␣CaM kinase II-binding domain of syntaxin 1, injected into presynaptic neurons, inhibits synaptic transmission, and that syntaxin 1 binds alternatively either ␣CaM kinase II or Munc-18, a presynaptic protein that was shown to block syntaxin from interacting with other SNAREs and forming the SNARE complex (Rizo and Sudhof, 2002).…”
Section: Figure 5 Effect Of Camentioning
confidence: 99%
“…Intracellular Binding of CaMKII by PPM1F-A variety of proteins has been shown to interact with CaMKII such as ␣-actinin-1 (38), syntaxin 1A (52), and the NR2A subunit of N-methyl-D-aspartate receptor (53). In particular, the catalytic subunit of protein phosphatase 2A has been found to coimmunoprecipitate with CaMKII from rat ventricular myocyte lysates (54), demonstrating a physical association of CaM kinase with one of its regulating phosphatases.…”
Section: Clone J4-3 As a Potential Cam Kinase Phosphatase-j4-3mentioning
confidence: 99%
“…In addition, several deletion mutants of PPM1F were assessed to identify the region responsible for binding. Because there are no amino acid sequences in PPM1F that match those identified in other proteins to be responsible for CaMKII binding (38,52,53), we initially utilized the mutants described earlier. Fulllength as well as mutants of Myc⅐PPM1F were transiently cotransfected with mCaMKII␣ into HEK293T, and immunoprecipitates were generated using anti-Myc antibody under stringent wash conditions.…”
Section: Clone J4-3 As a Potential Cam Kinase Phosphatase-j4-3mentioning
confidence: 99%